Branched-Chain Amino Acids Catabolism Pathway Regulation Plays a Critical Role in the Improvement of Leukopenia Induced by Cyclophosphamide in 4T1 Tumor-Bearing Mice Treated With Lvjiaobuxue Granule - Tian, Jun-sheng; Zhao, Hui-liang; Gao, Yao; Wang, Qi; Xiang, Huan; Xu, Xiang-ping; Huang, Sheng; Yan, Dong-lan; Qin, Xue-mei (Frontiers in Pharmacology, 2021)
Cyclophosphamide is a common tumor chemotherapy drug used to treat various cancers. However the resulting immunosuppression leads to leukopenia, which is a serious limiting factor in clinical application. Therefore, the introduction of immunomodulators as adjuvant therapy may help to reduce the hematological side effects of cyclophosphamide. Lvjiaobuxue granule has been widely used in clinical treatment of gynecological diseases such as anemia and irregular menstruation. Recently, it has been found to increase the function of white blood cells, but its mechanism of action is still unclear. The aim of this study was to investigate the pharmacological effect of Lvjiaobuxue granule on cyclophosphamide induced leukopenia in 4T1 tumor-bearing mice, to study its mechanism by means of 1H-NMR metabonomics, biological network analysis and molecular biology, and to completely understand the metabolic process for the function of Lvjiaobuxue granule on the leukopenia after cancer chemotherapy. Cyclophosphamide was used to establish the leucopenia model in 4T1 tumor-bearing mice and the content of white blood cells, red blood cells, hemoglobin, platelets, and other routine blood indexes are measured. The changes of endogenous metabolites in spleen analyzed by the 1H-NMR metabolomics technique were investigated the regulation effect of Lvjiaobuxue granule in mice with leukopenia. Afterward, the chemical components-targets-differential metabolites network of Lvjiaobuxue granule was constructed by the use of biological targets network, thus leucopenia-relevant metabolism pathways were dissected. Finally, the results of metabonomics and biological target network analysis were verified at the molecular level. The blood routine parameters and organ indexes levels of leucopenia model in 4T1 tumor-bearing mice were improved by Lvjiaobuxue granule. The metabolomic study revealed that 15 endogenous metabolites in mice spleen were considered as potential biomarkers of Lvjiaobuxue granule for their protective effect. Integrated analysis of metabolomics and biological targets network indicated that Lvjiaobuxue granule exerted the leukocyte elevation activity by inhibiting the BCAAs degradation pathway and increasing the levels of valine, leucine and isoleucine. Lvjiaobuxue granule exert obvious pharmacological effects on the leukopenia model of 4T1 tumor-bearing mice induced by cyclophosphamide, which could be mediated by regulating the branched-chain amino acid degradation pathway and the levels of valine, leucine and isoleucine.